Artificial Intelligence-Assisted Systematic Literature Reviews in Metabolic Phenotyping: A Methodological Framework and Validation Study - Maartje Cox; Javier Osorio Mosquera; Shaimaa Khandaker; Samuele Sala; Julien Wist; Jeremy K. Nicholson; Elaine Holmes; Timothy Fairchild; Nathan G. Lawler (Phenomics, 2026)
Systematic literature reviews are widely acknowledged to be at the top of most evidence hierarchies but are very time-consuming and labour-intensive. The advent of artificial intelligence (AI) offers possibilities to accelerate the review process. We propose a systematic literature review protocol that incorporates AI and evaluate the accuracy of AI against a human-constructed gold standard. Human researchers performed a systematic literature review on the PubMed metabolomic literature investigating Long COVID. OpenAI model o3-mini was then used via the application programming interface to carry out the three key stages of a systematic literature review: 1) screening articles for inclusion criteria, 2) evaluating articles' risk of bias (RoB) using a customised metabolomics tool based on well-established quality criteria, and 3) extracting data from articles. The performance of AI was evaluated against a manually created reference by the assessment of accuracy, negative predictive value, precision, sensitivity, specificity, F1 score, and Cohen's kappa. Out of the 320 identified articles, 33 met all inclusion criteria. AI performed screening, RoB assessment, and data extraction with mean accuracies of 92.7% ± 4.9%, 91.9% ± 5.9%, and 92.0% ± 9.2%, respectively, in ~ 10 h and at a cost of ~ 15.35 USD, while human reviewers took ~ 116 h, equivalent to ~ 2000 USD at minimum wages, to complete these steps in duplicate. OpenAI model o3-mini can independently complete the three main stages of systematic literature reviews in the metabolomics domain, thus considerably reducing the time to complete such reviews, at minimal cost. Nonetheless, human reviewers should always verify the AI-generated output to ensure robustness.

Measuring changes in environmental radiological background from construction of an advanced nuclear reactor testing facility - Jim Drachenberg; James E. Johnstone; Gage McClaine; Rusty S. Towell; Jared Barker; Neddy Chepkoech; Dale Cox; John C. Dalton; T.L. Head; Timothy J. Kennedy; Kim L. Pamplin; Jackson Shoultz; et al. (Journal of Environmental Radioactivity, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Assessing nonpoint-source uranium pollution in an irrigated stream-aquifer system - Ibraheem A. Qurban; Timothy K. Gates; Eric D. Morway; John T. Cox; Jeremy T. White; Ryan T. Bailey; Michael N. Fienen (Science of The Total Environment, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Island colonisation leads to rapid behavioural and morphological divergence in Anolis lizards - Daniel J. Nicholson; Robert J. Knell; Edita Folfas; Lauren K. Neel; Zachariah Degon; Madeline DuBois; Xochitl Ortiz-Ross; Albert K. Chung; John David Curlis; Timothy J. Thurman; W. Owen McMillan; Trenton W. J. Garner; et al. (Evolutionary Ecology, 2023)

The spontaneous mouse mutant low set ears (Lse) is caused by tandem duplication of Fgf3 and Fgf4 - Alana Luzzio; Sarah Edie; Kristina Palmer; L. Brianna Caddle; Rachel Urban; Leslie O. Goodwin; Ian C. Welsh; Laura G. Reinholdt; David E. Bergstrom; Timothy C. Cox; Leah Rae Donahue; Stephen A. Murray (Mammalian Genome, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Emerging Technologies and Approaches for In Situ, Autonomous Observing in the Arctic - Craig Lee; Michael DeGrandpre; John Guthrie; Victoria Hill; Ron Kwok; James Morison; Christopher Cox; Hanumant Singh; Timothy Stanton; Jeremy Wilkinson (Oceanography, 2022)
Understanding and predicting Arctic change and its impacts on global climate requires broad, sustained observations of the atmosphere-ice-ocean system, yet technological and logistical challenges severely restrict the temporal and spatial scope of observing efforts. Satellite remote sensing provides unprecedented, pan-Arctic measurements of the surface, but complementary in situ observations are required to complete the picture. Over the past few decades, a diverse range of autonomous platforms have been developed to make broad, sustained observations of the ice-free ocean, often with near-real-time data delivery. Though these technologies are well suited to the difficult environmental conditions and remote logistics that complicate Arctic observing, they face a suite of additional challenges, such as limited access to satellite services that make geolocation and communication possible. This paper reviews new platform and sensor developments, adaptations of mature technologies, and approaches for their use, placed within the framework of Arctic Ocean observing needs.

Pathogenic variants in CDH11 impair cell adhesion and cause Teebi hypertelorism syndrome - Dong Li; Michael E. March; Paola Fortugno; Liza L. Cox; Leticia S. Matsuoka; Rosanna Monetta; Christoph Seiler; Louise C. Pyle; Emma C. Bedoukian; María José Sánchez-Soler; Oana Caluseriu; Katheryn Grand; et al. (Human Genetics, 2021)

Rapamycin treatment attenuates age-associated periodontitis in mice - Jonathan Y. An; Ellen K. Quarles; Surapat Mekvanich; Alex Kang; Anthony Liu; Danielle Santos; Richard A. Miller; Peter S. Rabinovitch; Timothy C. Cox; Matt Kaeberlein (GeroScience, 2017)

Genetic resilience to amyloid related cognitive decline - Timothy J. Hohman; Logan Dumitrescu; Nancy J. Cox; Angela L. Jefferson (Brain Imaging and Behavior, 2017)

Chemical characterization and in vitro toxicity of diesel exhaust particulate matter generated under varying conditions - Julie Richman Fox; David P. Cox; Bertram E. Drury; Timothy R. Gould; Terrance J. Kavanagh; Michael H. Paulsen; Lianne Sheppard; Christopher D. Simpson; James A. Stewart; Timothy V. Larson; Joel D. Kaufman (Air Quality, Atmosphere & Health, 2015)

In-silico QTL mapping of postpubertal mammary ductal development in the mouse uncovers potential human breast cancer risk loci - Darryl L. Hadsell; Louise A. Hadsell; Walter Olea; Monique Rijnkels; Chad J. Creighton; Ian Smyth; Kieran M. Short; Liza L. Cox; Timothy C. Cox (Mammalian Genome, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

No evidence for cumulative effects in a Dnmt3b hypomorph across multiple generations - Neil A. Youngson; Trevor Epp; Amity R. Roberts; Lucia Daxinger; Alyson Ashe; Edward Huang; Krystal L. Lester; Sarah K. Harten; Graham F. Kay; Timothy Cox; Jacqueline M. Matthews; Suyinn Chong; et al. (Mammalian Genome, 2013)

Relationships between stream phosphorus concentrations and drainage basin characteristics in a watershed with poultry farming - Timothy J. Cox; Bernard A. Engel; Roger L. Olsen; J. B. Fisher; Andrew D. Santini; Brian J. Bennett (Nutrient Cycling in Agroecosystems, 2013)

Biophysical feedback mediates effects of invasive grasses on coastal dune shape - Phoebe L. Zarnetske; Sally D. Hacker; Eric W. Seabloom; Peter Ruggiero; Jason R. Killian; Timothy B. Maddux; Daniel Cox (Ecology, 2012)
Vegetation at the aquatic–terrestrial interface can alter landscape features through its growth and interactions with sediment and fluids. Even similar species may impart different effects due to variation in their interactions and feedbacks with the environment. Consequently, replacement of one engineering species by another can cause significant change in the physical environment. Here we investigate the species‐specific ecological mechanisms influencing the geomorphology of U.S. Pacific Northwest coastal dunes. Over the last century, this system changed from open, shifting sand dunes with sparse vegetation (including native beach grass, Elymus mollis ), to densely vegetated continuous foredune ridges resulting from the introduction and subsequent invasions of two nonnative grass species ( Ammophila arenaria and Ammophila breviligulata ), each of which is associated with different dune shapes and sediment supply rates along the coast. Here we propose a biophysical feedback responsible for differences in dune shape, and we investigate two, non‐mutually exclusive ecological mechanisms for these differences: (1) species differ in their ability to capture sand and (2) species differ in their growth habit in response to sand deposition. To investigate sand capture, we used a moveable bed wind tunnel experiment and found that increasing tiller density increased sand capture efficiency and that, under different experimental densities, the native grass had higher sand capture efficiency compared to the Ammophila congeners. However, the greater densities of nonnative grasses under field conditions suggest that they have greater potential to capture more sand overall. We used a mesocosm experiment to look at plant growth responses to sand deposition and found that, in response to increasing sand supply rates, A. arenaria produced higher‐density vertical tillers (characteristic of higher sand capture efficiency), while A. breviligulata and E. mollis responded with lower‐density lateral tiller growth (characteristic of lower sand capture efficiency). Combined, these experiments provide evidence for a species‐specific effect on coastal dune shape. Understanding how dominant ecosystem engineers, especially nonnative ones, differ in their interactions with abiotic factors is necessary to better parameterize coastal vulnerability models and inform management practices related to both coastal protection ecosystem services and ecosystem restoration.

Groundwater-level response to land-use change and the implications for salinity management in the West Moorabool River catchment, Victoria, Australia - Peter G. Dahlhaus; Timothy J. Evans; Erica L. Nathan; Jim W. Cox; Craig T. Simmons (Hydrogeology Journal, 2010)

Spatial distribution of lead concentrations in urban surface soils of New Orleans, Louisiana USA - Michael T. Abel; Burton Suedel; Steven M. Presley; Thomas R. Rainwater; Galen P. Austin; Stephen B. Cox; Les N. McDaniel; Richard Rigdon; Timothy Goebel; Richard Zartman; Blair D. Leftwich; Todd A. Anderson; et al. (Environmental Geochemistry and Health, 2010)

Genetic analysis of avian influenza A viruses isolated from domestic waterfowl in live-bird markets of Hanoi, Vietnam, preceding fatal H5N1 human infections in 2004 - Samadhan J. Jadhao; Doan C. Nguyen; Timothy M. Uyeki; Michael Shaw; Taronna Maines; Thomas Rowe; Catherine Smith; Lien P. T. Huynh; Ha K. Nghiem; Diep H. T. Nguyen; Hang K. L. Nguyen; Hanh H. T. Nguyen; et al. (Archives of Virology, 2009)

Gene expression analysis in a canine model of X-linked Alport syndrome - Kimberly A. Greer; Marnie A. Higgins; Melissa L. Cox; Timothy P. Ryan; Brian R. Berridge; Clifford E. Kashtan; George E. Lees; Keith E. Murphy (Mammalian Genome, 2006)

Thermal tolerances of two stream invertebrates exposed to diumally varying temperature - Timothy J. Cox; J. Christopher Rutherford (New Zealand Journal of Marine and Freshwater Research, 2000)
For two key New Zealand freshwater invertebrates (the mayfly Deleatidium autumnale and the snail Potamopyrgus antipodarum ) the upper thermal tolerances were measured in the laboratory under both constant and diumally varying temperatures. At constant temperature 50% mortality in 96 h ( const LT 50 ) occurred at 24.2 ± 0.9°C for mayflies and 31.0 ± 0.6°C for snails: values similar to previously published estimates (Quinn et al. 1994). For diurnally varying temperatures (daily amplitude 10°C) 50% mortality occurred when the daily mean temperature was 21.9 ± 0.7°C (mayflies) and 28.6 ± 0.4°C (snails) which is c. 10% (2.5 ± 1.3°C) lower than the const LT 50 . Conversely, 50% mortality occurred when the daily maximum temperature was 26.9 ± 0.7°C (mayflies) and 33.6 ± 0.4°C (snails) which is c. 10% (2.5 ± 1.3°C) higher than the const LT 50 . Many published temperature limits for stream organisms are derived from constant temperature experiments. Our results indicate that such limits should be applied to a temperature midway between the daily average and the daily maximum of a diurnal profile.

Predicting the effects of time‐varying temperatures on stream invertebrate mortality - Timothy J. Cox; J. Christopher Rutherford (New Zealand Journal of Marine and Freshwater Research, 2000)
Stream managers often need to predict the impacts of high and time‐varying temperature on key stream invertebrates. A simplified model has been developed and calibrated using mortality observations made at constant temperature for two important New Zealand stream invertebrates: the snail Potamopyrgus antipodarum and the mayfly Deleatidium autumnale . A close fit was obtained for Deleatidium but Potamopyrgus showed evidence of acclimation during the 96‐h tests. The model successfully predicted the mortality observed when temperature varied diurnally by ±5°C in seven experiments but over‐estimated mortality in the eighth. The experiments used to calibrate and test the model were performed on test animals collected in winter (April‐June) and acclimated at 16–17°C. The model was less successful at predicting mortality on Deleatidium collected in summer (December‐January) and/or acclimated at 21–22°C. The likely reason is that the model, calibrated using winter data, does not account for summer acclimation.